2007
DOI: 10.1016/j.ajog.2007.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulators plus antibiotics delay preterm delivery after experimental intraamniotic infection in a nonhuman primate model

Abstract: The combination of ampicillin + dexamethasone + indomethacin suppressed inflammation and significantly prolonged gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 37 publications
(11 reference statements)
6
77
2
Order By: Relevance
“…As such, we conclude that the administration of antibiotics alone may not be sufficient to resolve intrauterine inflammation. Again these data are consistent with previous work undertaken in nonhuman primates, as well as data from clinical studies (11,46,47).…”
Section: Discussionsupporting
confidence: 82%
“…As such, we conclude that the administration of antibiotics alone may not be sufficient to resolve intrauterine inflammation. Again these data are consistent with previous work undertaken in nonhuman primates, as well as data from clinical studies (11,46,47).…”
Section: Discussionsupporting
confidence: 82%
“…We have recently demonstrated that ampicillin plus dexamethasone and indomethacin delayed preterm birth induced by Group B Streptococcus by 8 days. 9 It is possible that TLR blockade of the innate immune response, in combination with antibiotics, will result in a longer latency period or perhaps even prevention of infection-induced preterm birth.…”
Section: Commentmentioning
confidence: 99%
“…7,8 Furthermore, dexamethasone and indomethacin administered with antibiotics prolonged gestation and suppressed amniotic fluid cytokine and prostaglandin production in response to experimental IAI with GBS. 9 These immunomodulators targeted cytokine and prostaglandin production, which likely represent downstream events in the inflammatory cascade and may not protect the fetus from adverse sequelae of intrauterine infection. Further inhibition of uterine activity and the fetal inflammatory response could result from blockade of the initial events in immune recognition of bacteria mediated by toll-like receptors (TLR), which are the principal and earliest sensors of bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many authors call for the development of biomarkers to assess risk of adverse pregnancy outcomes early in gestation in BV-positive women at high risk of adverse pregnancy outcome [2][3][4]47,54,55]. Among candidate biomarkers, inflammatory factors seem promising owing to the evidence implicating of inflammatory pathways in PTB and labor (such as the infiltration by macrophages and neutrophils into the myometrium and cervix) [44,56].…”
Section: Discussionmentioning
confidence: 99%